Multisystemic crisis and the exhaustion of the globalizing model: impact on artisanal fishing in Nayarit, México - Giraldo Calderón, Patricia Elena (2025)
This article analyzes the implications, transformations, and future prospects of artisanal fishing on the coast of Nayarit, Mexico, considering globalization as a political, economic, and ideological framework. Through a case study of its artisanal fishers, the research examines the evolution of this activity across three periods: national expansion and the cooperative export model (1938-1981); the global market, financialization, and economic liberalization (1982-2016); and the exhaustion of globalization due to multisystemic crises (2017-2025). The analysis reveals a trajectory initially marked by the success of the cooperative model, followed by a crisis with negative environmental, economic, political, and social impacts on the fishers. The decline of globalization, evidenced by the deepening of inequalities, trade protectionism, and productive fragmentation, poses significant challenges for the future of artisanal fishing in the region, despite theprevious development achieved through cooperative organization.